2019
DOI: 10.1016/j.ebiom.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a TP53-associated immune prognostic model for hepatocellular carcinoma

Abstract: Background TP53 mutation is the most common mutation in hepatocellular carcinoma (HCC), and it affects the progression and prognosis of HCC. We investigated how TP53 mutation regulates the HCC immunophenotype and thus affects the prognosis of HCC. Methods We investigated TP53 mutation status and RNA expression in different populations and platforms and developed an immune prognostic model (IPM) based on immune-related genes that were differentially expressed between TP5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
244
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(250 citation statements)
references
References 62 publications
6
244
0
Order By: Relevance
“…Another study also constructed a sixgene prognostic signature for HCC overall survival prediction based on gene expression data from TCGA [33]. A recent study investigating the prognostic value of TP53-associated immune genes in HCC identified and validated a two-gene (TREM1 and EXO1) prognostic model [34]. However, these studies did not use a large number of samples to comprehensively explore the relationship between immune genes and prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also constructed a sixgene prognostic signature for HCC overall survival prediction based on gene expression data from TCGA [33]. A recent study investigating the prognostic value of TP53-associated immune genes in HCC identified and validated a two-gene (TREM1 and EXO1) prognostic model [34]. However, these studies did not use a large number of samples to comprehensively explore the relationship between immune genes and prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…40 This may result in increased immunosuppressive cells (e.g., regulatory T cells and tumor-associated macrophages), decreased immunoreactive cells (e.g., T cells follicular helper), and increased expression of immunosuppressive molecules (e.g., CTLA-4 and PD-1) in the tumor. 41 PD-1 is a central regulator of T cells CD8 exhaustion and blockade of this inhibitory pathway enhances T cell immunity in several different types of cancers. 42,43 Thus, we hypothesized that patients in different groups would have different immunotherapeutic responses.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Additionally, several immune prognostic signatures have been reported to predict the prognosis of patients with cancer, such as lung cancer, 13 ovarian cancer, 14 colorectal cancer, 15 and hepatocellular carcinoma. 16 These studies indicate that IRGs or TIME can serve as promising biomarkers for estimating survival in corresponding cancer. However, limited studies have explored whether immune-related genes (IRGs) or TIME could be indicators for the prognosis of CC.…”
Section: Introductionmentioning
confidence: 93%